2010
DOI: 10.1039/c0py00097c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and in vitro degradation of 3D-microstructured poly(ε-caprolactone) resins

Abstract: Poly(3-caprolactone)s of controlled molecular weight and low molecular weight distribution were prepared via anionic ring-opening polymerization using a tetra-functional initiator. The prerequisite for crosslinking was achieved by end-capping of the arms with acrylate groups. Novel biodegradable polyester resins were prepared by crosslinking of the functional polyesters via Michael addition using amino-telechelic poly(tetrahydrofuran). Three-dimensional microstructuring via replica molding shows the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…Previous accelerated degradation studies also have demonstrated that PCL networks degrade faster than linear PCL when immersed in an alkaline medium [18]. Theiler et al [23] related an increase of the degradation rate with the higher hydrophilicity and lower crystallinity of PCL networks as compared with linear PCL. Harrison et al [24] studied how crystallinity and water absorption affect the degradation rate.…”
Section: Weight Loss and Swollen Degreementioning
confidence: 87%
“…Previous accelerated degradation studies also have demonstrated that PCL networks degrade faster than linear PCL when immersed in an alkaline medium [18]. Theiler et al [23] related an increase of the degradation rate with the higher hydrophilicity and lower crystallinity of PCL networks as compared with linear PCL. Harrison et al [24] studied how crystallinity and water absorption affect the degradation rate.…”
Section: Weight Loss and Swollen Degreementioning
confidence: 87%
“…Star-shaped poly(caprolactone)s bearing acrylate end groups were prepared as previously described (Hans et al, 2009;Theiler et al, 2010). In this paper the successful biofunctionalization of such polymers via Michael-type addition using L-arginin ethyl ester or L-cysteine ethyl ester as model biomolecules is shown.…”
Section: Resultsmentioning
confidence: 99%
“…Star-shaped functional poly(e-caprolactone)s (sPCL-A 2a-f) used in this work have the following characteristics: (Hans et al 2009;Theiler et al, 2010). e-Caprolactone (CL, !99%, Fluka, Buchs, Switzerland) was stirred over CaH 2 for 24 h, condensed onto molecular sieves (4 Å ), and kept in a Schlenk flask under argon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations